Kumpulan data fauna ikan air tawar di perairan kawasan Gunung Galunggung - Haryono, Haryono; Wahyu Dewantoro, Gema; Wulan, Sri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
In this data article, we present scientific data on the diversity of freshwater fish fauna in the waters of the Galunggung Mountain area. The Galunggung area serves as a potential habitat for freshwater fish due to the presence of many rivers and streams. Fish sampling was based on catch per unit effort (CPUE), mainly using electrofishing, gill nets, and hand nets. A total of 24 species were recorded during the survey. Seven fish species, namely Amphilophus alfari, Amphilophus citrinellus, Andinoacara pulcher, Andinoacara rivulatus, Cichlasoma spilurus, Cichlasoma uropthalmum, and Poecilia reticulata, are included in this dataset. Additionally, data from 10 research station locations and the Galunggung crater lake, which is the highest research location, are also included in this dataset. The data in this article can be found in the National Scientific Repository, covering the research locations, the fish species discovered, and several documented fish specimen photos. Regarding its potential utilization, this data can be used as a basis for policy formulation in the fisheries sector and when conducting a review of the fish fauna in the Galunggung Mountain area.